Geological characteristics and coalbed methane adsorbability of shallow coal rock in Qinshui Basin, China - Ping Guo; Xiaojun Tang; Lei Wen; Bin Wu; Feng Luo; Yanbao Liu (Journal of Petroleum Exploration and Production Technology, 2024)
Abstract The coal-rock reservoir exhibits a dual porous medium characteristic, where fractures are the primary contributor to permeability, while pore structure influences the gas adsorption properties of coal rock. Gas adsorption induces swelling in the coal matrix, leading to a reduction in fracture width and subsequently causing decreased permeability and reduced well production. Investigating the impact of geological characteristics of coal-rock on gas adsorption and desorption properties can enhance our understanding of the patterns governing changes in coal-layer production. This study focused on the 3# coal seam in China's Qinshui Basin as its research subject. It involved an analysis of mineral composition, physical properties, gas content, and pore structure characteristics to explore the adsorption traits of different gases and conduct experimental studies on variations in gas adsorption and desorption capabilities under diverse conditions. The research findings suggest that the coal rock in the study area is primarily characterized by micropores and small pores, with well-developed larger pores and fractures. The pore connectivity is somewhat limited, and the predominant pore size ranges from 100 to 200 nm. The average permeability measures 0.198 × 10–3 µm2, while the mean specific gas content stands at 21.7 m3/t. Analysis of the isothermal adsorption curve reveals a substantial increase in adsorption when pressure falls below 3.5 MPa due to a steep slope; as pressure continues to rise, there is a gradual upward trend in adsorption until reaching 8 MPa, after which point adsorption increases slowly and stabilizes. Results from binary gas adsorption–desorption experiments indicate low desorption levels and rates for CO2 components compared to relatively higher desorption amounts and rates for CH4 components. Furthermore, it was observed that CO2 has a displacement effect on CH4; higher CO2 concentrations are more conducive to CH4 release and CO2 storage.